Ananalysis of Branding Strategies for Developing Creative Economy Based on the Regional Potential Resources (A Study in Bau-Bau City, Southeast Sulawesi) - Supriyadi, Supriyadi; Almana, La Ode; Hasnita, Nita (Budapest International Research and Critics University, 2022)
This study aimed to find out the regional advantage potential empirically and analyze branding strategies in order to encourage the acceleration of regional development that had the potential as a regional growth center, reduce development gaps between regions, and encourage regional growth, especially in Baubau City. This needed to be done as an effort to develop fast-growing strategic areas in the development of creative cities in the region. The key variable in this study was ecosystem-based creative economy branding, namely human resources, goods/services, markets, research, and development. The sampling method used was purposive sampling and snowball sampling. In this study, the concept of a creative economy branding strategy based on superior local resources was arranged using a ranking analysis of the creative economy sub-sector of Bau-Bau City.